Latin America after Mexico : quickening the pace - Burki, Shahid Javed (World Bank WashingtonUS, 1995)
Examines the Mexico peso crisis, its impact and the challenges that lie ahead. Discusses the causes of the crisis, the March 9 adjustment program and the likely effects of this episode. Presents an analysis of the main economic and institutional challenges for Latin American and the Caribbean Region in the years ahead. Discuses medium- and long-term growth prospects and provides conclusions.